PENGARUH PAJAK PROGRESIF TERHADAP PERILAKU KONSUMTIF, BASIS PAJAK, KEPATUHAN WAJIB PAJAK DAN PENDAPATAN DAERAH PROVINSI BALI - wisnu murthi, ngurah; kembar sribudi, made; Purbadharmaja, ida bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.12.TAHUN 2015, 2016)
The focus of research on the issue of progressive tax on automobiles in Bali. This policy aims to increase local revenue comes from vehicle taxes, in addition to reducing traffic congestion in cities such as Denpasar and Badung. The research objective to analyze the effect of progressive tax changes on consumer behavior, vehicle ownership (tax base), tax compliance and revenue estimates of Bali . This study used primary data sourced from taxpayers grouped respondents over the ownership of two units and more than two units of four-wheeled vehicles. The sample of respondents was taken as many as 100 people, using probability proportional to size sampling is based on vehicle ownership dispersed population in the district / city in Bali. Data were analyzed using pathway diagrams and structural equation modeling. The results show that changes in marginal tax burden has not been able to lower consumer behavior and the willingness of taxpayers in the ownership of the vehicle (the tax base), but the taxpayers still abiding in the payment of taxes on motor vehicles. Then based on estimates of the taxpayer, although there are changes in the progressive income tax expense increased in the region remains relatively small amount.
Keywords: progressive tax, taxpayer compliance dan revenue provincial